The psychometric assessment of the perma scale kinaray-a scale. - Dalapo, Mila Leona C.
This study is a pioneer study on the psychometric properties of the PERMA scale Kinaray-a version. It sought to establish validity and reliability as well as reproduce the item and factor loadings of the original scale. It is a 23-item scale using an 11-point scale starting from 0 to 10. The research utilized a mixed method approach. The test was administered to women in fisheries coming from several municipalities of Miagao, aging 20-59 years old. The PERMA scale was administered alongside Ryff?s 42-item Psychological Well-Being scale, Center for Epidemiologic Studies Depression Scale, Satisfaction with Life scale, and the Parallel PERMA scale. The results showed acceptable internal consistency and a significant positive correlation using parallel forms. The PERMA scale Kinaray-a version displayed a significant correlation with Ryff?s 42-item Psychological Well-Being scale exhibiting evidence of convergent validity.